The Relationship between Genes, Psychological Traits, and Political Participation. Issue 4 (6th May 2014) - Dawes, Christopher; Cesarini, David; Fowler, James H.; Johannesson, Magnus; Magnusson, Patrik K. E.; Oskarsson, Sven
<x xml:space="preserve">Abstract</x> Recent research demonstrates that a wide range of political attitudes, beliefs, and behaviors can be explained in part by genetic variation. However, these studies have not yet identified the mechanisms that generate such a relationship. Some scholars have speculated that psychological traits mediate the relationship between genes and political participation, but so far there have been no empirical tests. Here we focus on the role of three psychological traits that are believed to influence political participation: cognitive ability, personal control, and extraversion. Utilizing a unique sample of more than 2, 000 Swedish twin pairs, we show that a common genetic factor can explain most of the relationship between these psychological traits and acts of political participation, as well as predispositions related to participation. While our analysis is not a definitive test, our results suggest an upper bound for a proposed mediation relationship between genes, psychological traits, and political participation.